Perceived barriers to healthy lifestyle from the parental perspective of overweight and obese students - Shahsanai, Armindokht (J Educ Health Promot, 2019)
BACKGROUND: Over the last decades, childhood obesity has become a worldwide epidemic health problem. Identifying the barriers to a healthy lifestyle among children and adolescents is necessary for further effective intervention to prevent overweight and obesity. This study aims to assess the barriers to healthy lifestyle habits, including physical activity (PA), eating, and sleep among adolescents from the perspective of their parents. METHODS: In this cross-sectional study, the parents of obese and overweight middle school students were enrolled. Data were collected using a questionnaire about barriers of healthy nutrition and PA. RESULTS: Overall, 172 parents completed the questionnaire. Lack of access to affordable facilities for PA, lack of access to the appropriate place for PA, and lack of sufficient information on how to do or increase PA were the main barriers to PA. The barrier factors for healthy eating were media advertisement of unhealthy foods, lack of motivation to use healthy nutrition, and lack of adequate information about healthy eating. Regarding poor sleep, lack of knowledge about the benefits of sleep, prolonged watching television, and late sleep time of family members were reported as the main barriers. These findings were not statistically different according to the family socioeconomic level. CONCLUSION: Our findings propose that for improving healthy lifestyle in obese children and adolescents, access to facilities, and appropriate places for PA should be provided at the community level. Moreover, training parents and students about healthy lifestyle behaviors is necessary for families of all socioeconomic levels.